ChemInform Abstract: Synthesis and Use of Bimetals and Bimetal Oxides in Contaminants Removal from Water: A Review. Issue 49 (December 2015) - Fu, Fenglian; Cheng, Zihang; Lu, Jianwei
Abstract: Review: 183 refs.